A Finnish nationwide population-based study on the survival of patients with peripheral T-cell lymphoma - Reunamo, Taina; Kalashnikov, Ilja; Lahtela, Kreetta; Pollari, Marjukka; Viisanen, Leevi; Mannisto, Susanna; Jyrkkiö, Sirkku; Leppä, Sirpa (NATURE PORTFOLIO, 2026)
Peripheral T-cell lymphomas (PTCLs) represent a heterogeneous group of rare malignancies with poor survival; however, population-based long-term survival data remain limited. We conducted a nationwide study to estimate overall survival (OS) and relative survival (RS) among 915 patients diagnosed with PTCLs from 2002 - 2018 (57% males, median age 67 years) using the Finnish Cancer Registry. The most common subtypes included PTCL not otherwise specified (PTCL NOS; 37%), angioimmunoblastic T-cell lymphoma (AITL; 27%), and ALK-anaplastic large cell lymphoma (ALK-ALCL; 12%). Age > 60 years at diagnosis, advanced stage, and male sex were associated with poorer OS. Five-year OS and RS were better in patients with ALK + ALCL compared with PTCL NOS (5-year OS: 85% vs 30%). Patients with ALK- ALCL had a favorable 5-year OS compared to PTCL NOS (46% vs 30%), while those with enteropathy-associated T-cell lymphoma (EATL) demonstrated worse OS (15%). There was no improvement in RS from 2002 - 2012 to 2013 - 2018. OS was better in patients (excluding ALK + ALCL) receiving high-dose chemotherapy (HDCT) compared to those for whom HDCT was not planned (HR 0.61; 95% CI 0.47 - 0.80). We conclude that RS did not improve during the study period; however, consolidation with HDCT for eligible patients resulted in favorable survival.